2020
DOI: 10.1111/ans.15421
|View full text |Cite
|
Sign up to set email alerts
|

International consensus definition of low anterior resection syndrome

Abstract: Background Low anterior resection syndrome (LARS) is pragmatically defined as disordered bowel function after rectal resection leading to a detriment in quality of life. This broad characterization does not allow for precise estimates of prevalence. The LARS score was designed as a simple tool for clinical evaluation of LARS. Although the LARS score has good clinical utility, it may not capture all important aspects that patients may experience. The aim of this collaboration was to develop an international con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The resection of the rectum, division of the coccygeus muscle, and/or damage to the nerve supply can impair rectal function. The remaining rectum is small and does not function properly, and the hypermotility of the remnant colon can affect the manifestation of urge fecal incontinence (7,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resection of the rectum, division of the coccygeus muscle, and/or damage to the nerve supply can impair rectal function. The remaining rectum is small and does not function properly, and the hypermotility of the remnant colon can affect the manifestation of urge fecal incontinence (7,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It can be described as a "disordered bowel function after rectal resection, leading to a detriment in quality of life." (14)(15)(16)(17). The etiology of LARS is poorly understood, and it seems that the anatomical components and physiological functions of normal defecation, which may be damaged during surgery, are not well established (9,18).…”
Section: Introductionmentioning
confidence: 99%
“…OAR for patients with rectal cancer include bladder, bowel, pelvic bone marrow, nervous tissue, skin, and genitalia. Acquired radiation dose to these OAR can result in adverse events which can affect survival and quality of life [16] , [17] , [18] , [19] . As demonstrated in the RAPIDO trial, considerable toxicity was observed in the preoperative period with 48 % of patients in the SCRT arm experiencing grade 3+ toxicity [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction translates into impairment of patients' daily activities that end up in "toilet-dependence" and deterioration of their quality of life, even in the long-term (9, 10). These concerns have motivated the development of a new LARS Patient-Reported Outcome Measure tool that includes symptoms and consequences (11).…”
Section: Introductionmentioning
confidence: 99%